The impact of bundled payment on the economic burden and satisfaction of patients in Close-Knit County Medical Community in China - Guo, Yanhong; Qian, Jialin; Li, Xin; Wang, Jian; Zhu, Liangying; Huang, Erdan; Zhang, Yanchun; Nong, Sheng (Frontiers in Public Health, 2025)
BackgroundChina is setting up a Close-Knit County Medical Community (CCMC) to connect county hospitals, township health centers, and village clinics. The medical insurance agency will count the number of insured people in the CCMC area and distribute funds to the community as a whole. Then, the county hospital will work with local health facilities to decide how to use these funds. This reform aims to improve primary healthcare services, lower medical costs, support residents’ health, and boost their satisfaction with healthcare.MethodsThis study looked at data from counties in China monitored by County Medical Communities from 2018 to 2022. We used difference-in-differences (DID) to analyze how bundled payments affected patients’ financial burdens, the income of healthcare providers and the satisfaction of patients and healthcare providers.ResultsThe bundled payment policy had no significant effect on the average cost per discharged patient (p > 0.05). In 2022, the average outpatient expenses increased by 17.58 yuan (p < 0.05), while in 2021, the actual reimbursement rates for hospitalization costs rose by 2.18% (p < 0.05). The policy also significantly increased the per-capita income of providers in county hospitals and primary care institutions in 2021 (p < 0.01); however, we cannot quantitatively isolate the precise marginal contribution of the bundled payment policy to the observed income increases. Additionally, it had no significant impact on the satisfaction levels of either patients or healthcare providers (p > 0.05).ConclusionBundled medical insurance payments in the CCMC do not add financial stress for patients and help low-income families. They also boost the income of healthcare providers. However, there is still a need for improvements to enhance overall satisfaction with the healthcare system.